Endothelial Ion Channels and Cell-Cell Communication in the Microcirculation - Jackson, William F. (Frontiers in Physiology, 2022)
Endothelial cells in resistance arteries, arterioles and capillaries express a diverse array of ion channels that contribute to cell-cell communication in the microcirculation. Endothelial cells are tightly electrically coupled to their neighboring endothelial cells by gap junctions allowing ion channel-induced changes in membrane potential to be conducted for considerable distances along the endothelial cell tube that lines arterioles and forms capillaries. In addition, endothelial cells may be electrically coupled to overlying smooth muscle cells in arterioles and to pericytes in capillaries via heterocellular gap junctions allowing electrical signals generated by endothelial cell ion channels to be transmitted to overlying mural cells to affect smooth muscle or pericyte contractile activity. Arteriolar endothelial cells express inositol 1,4,5 trisphosphate receptors (IP3Rs) and transient receptor vanilloid family member 4 (TRPV4) channels that contribute to agonist-induced endothelial Ca2+ signals. These Ca2+ signals then activate intermediate and small conductance Ca2+-activated K+ (IKCa and SKCa) channels causing vasodilator-induced endothelial hyperpolarization. This hyperpolarization can be conducted along the endothelium via homocellular gap junctions and transmitted to overlying smooth muscle cells through heterocellular gap junctions to control the activity of voltage-gated Ca2+ channels and smooth muscle or pericyte contraction. The IKCa and SKCa-induced hyperpolarization may be amplified by activation of inward rectifier K+ (KIR) channels. Endothelial cell IP3R- and TRPV4-mediated Ca2+ signals also control the production of endothelial cell vasodilator autacoids such as NO, PGI2 and epoxides of arachidonic acid contributing to control of overlying vascular smooth muscle contractile activity. Cerebral capillary endothelial cells lack IKCa and SKCa but express KIR channels, IP3R, TRPV4 and other Ca2+ permeable channels allowing capillary-to-arteriole signaling via hyperpolarization and Ca2+. This allows parenchymal cell signals to be detected in capillaries and signaled to upstream arterioles to control blood flow to capillaries by active parenchymal cells. Thus, endothelial cell ion channels importantly participate in several forms of cell-cell communication in the microcirculation that contribute to microcirculatory function and homeostasis.